2013
DOI: 10.1021/jf400981x
|View full text |Cite
|
Sign up to set email alerts
|

Maxima in Antioxidant Distributions and Efficiencies with Increasing Hydrophobicity of Gallic Acid and Its Alkyl Esters. The Pseudophase Model Interpretation of the “Cutoff Effect”

Abstract: Antioxidant (AO) efficiencies are reported to go through maxima with increasing chain length (hydrophobicity) in emulsions. The so-called "cutoff" after the maxima, indicating a decrease in efficiency, remains unexplained. This paper shows, for gallic acid (GA) and propyl, octyl, and lauryl gallates (PG, OG, and LG, respectively), that at any given volume fraction of emulsifier, the concentrations of antioxidants in the interfacial region of stripped corn oil emulsions and their efficiency order follow PG > GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
131
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(152 citation statements)
references
References 56 publications
(237 reference statements)
20
131
1
Order By: Relevance
“…Using a broad range of homologous series of antioxidants in dispersed lipid models and cultured cells, it has been demonstrated that the antioxidant activity increases progressively with increasing chain length up to a critical point, beyond which the activity of the compounds decreases (Figure 4). Since its first mention (Laguerre et al 2009), this cut-off effect for antioxidants has been the subject of extensive research in lipid dispersions (Alemán et al 2015;Costa et al 2015;Laguerre et al 2010;Lee et al 2013;Losada-Barreiro et al 2013;Medina et al 2009;Panya et al 2012;Sørensen et al 2012Sørensen et al , 2014Sørensen et al , 2015 and cellular models , Laguerre et al 2011, Munoz-Marin et al 2013) as well as of review articles (Laguerre et al 2013a(Laguerre et al ,b, 2015Shahidi & Zhong 2011;Zhao et al 2015). Table 1 gives some examples of the experimental confirmations of the occurrence of a cut-off effect.…”
Section: Figurementioning
confidence: 99%
“…Using a broad range of homologous series of antioxidants in dispersed lipid models and cultured cells, it has been demonstrated that the antioxidant activity increases progressively with increasing chain length up to a critical point, beyond which the activity of the compounds decreases (Figure 4). Since its first mention (Laguerre et al 2009), this cut-off effect for antioxidants has been the subject of extensive research in lipid dispersions (Alemán et al 2015;Costa et al 2015;Laguerre et al 2010;Lee et al 2013;Losada-Barreiro et al 2013;Medina et al 2009;Panya et al 2012;Sørensen et al 2012Sørensen et al , 2014Sørensen et al , 2015 and cellular models , Laguerre et al 2011, Munoz-Marin et al 2013) as well as of review articles (Laguerre et al 2013a(Laguerre et al ,b, 2015Shahidi & Zhong 2011;Zhao et al 2015). Table 1 gives some examples of the experimental confirmations of the occurrence of a cut-off effect.…”
Section: Figurementioning
confidence: 99%
“…polarity) of the reaction site. The k I values obtained in octane based emulsions are much lower than those obtained in corn oil emulsions [22], …”
Section: Resultsmentioning
confidence: 58%
“…The general picture that arises from those studies is that the percentage of antioxidant in the interfacial region increases upon increasing the emulsifier volume fraction. However, we demonstrated recently for a series of homologous AOs with increasing alkyl chain length [22] that the percentage of AO in the interfacial region does not correlate with their hydrophobicity and an increase in the hydrophobicity may lead to a decrease in their concentration in the interfacial region. Note that an increase in the surfactant volume fraction implies an increase in the interfacial volume, and thus decreases the interfacial molarity of the antioxidant at constant ratio of oil to water, as we have shown here.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations